Development of the St. Petersburg Tourism Cluster in the Framework of Creating New Attractiveness Factors for the Hotel Chain Through Mid-Range Apartments - E. А. Podolskaya; О. N. Misko (Управленческое консультирование)
The purpose of this study is to identify the characteristic features of the process in which the tourism industry of St. Petersburg is becoming more popular due to the spread of middle-class apartments. The article considers the problems of the tourism industry associated with the consequences of the pandemic, as well as with the political and economic pressure of other countries. Possible solutions are proposed due to concessional lending for the construction of hotels and apart-hotels. As a result, the reasons why apartments are in high demand in the Russian Federation were revealed. We believe that the analysis carried out indicates the expediency of investing in the construction of apartments and bringing the lease into an official type of activity. In the future, this will lead to an increase in the quality of service to tourists, an increase in the level of satisfaction and an increase in the income of the industry. It is also necessary to introduce concessional lending programs, which in the long term will lead to the stimulation of the tourism industry, as well as related industries, including construction. The latter, in turn, is a driver of economic processes taking place in the Russian Federation.